INTEGRASI METODE LATIHAN SELF TALK DALAM LATIHAN DAYA TAHAN UNTUK MENINGKATKAN VO2MAXATLET SEPATU RODA JARAK MENENGAH - Atep Deni, - (2023)
Atep Deni. NIM. 1808689. Thesis: Integration of self talk training methods in endurance training to increase VO2Max in middle distance speed inline skate athletes. This thesis was supervised by Prof. Dr. Komarudin, M.Pd. and Dr. H. Dikdik Jafar Sidik, M.Pd. Graduate School Sports Education. Indonesian education university. This study aims to test the self talk training method in the endurance method to increase athletes' VO2Max. This research is an experimental research with a pretest- post test two design. The sample consisted of 36 athletes consisting of 24 males and 12 females aged 14 to 20 years who had trained for 4 years to 7 years. This study was divided into two groups which were taken randomly. 18 children in the experimental group were given a self-talk training program that integrated interval training, 18 athletes in a different group were given a self-talk training program that integrated fartlek training. The results obtained are: 1) The self-talk training model that integrates interval training increases VO2Max with the overall average treatment design results increasing 16% - 30%. The self talk training program integrated with fartlek training with an overall average result experienced an increase of 5% -11%. The self talk exercise method integrated with interval training was better than the self talk method integrated with fartlek exercises. Keywords: Self talk training method, Endurance training method, Roller skates athlete.